Prosthechea tinukiana sp. nov. (Orchidaceae: Laeliinae): an update of the Prosthechea prismatocarpa complex - Bogarín Chaves, Diego Gerardo (2015)
We describe and illustrate a new species of Prosthechea from Costa Rica. The species is similar to Prosthechea ionocentra, but it is easily distinguishable by its inflorescence originating from the penultimate mature pseudobulb; its purple spotted sepals and petals; the cordate, acute labellum; the disc with two longer, narrower keels; the stigmatic arms of the column, which are convergent and rounded; and the narrower stigma. Differences from other related species are given and discussed. Data on distribution, habitat and ecology, etymology, and phenology are provided. An updated key to the species of the Prosthechea prismatocarpa complex is presented.